Development of a dry powder formulation for pulmonary delivery of azithromycin-loaded nanoparticles - Alison Tatiana Madrid Sani; Alison Tatiana Madrid Sani; Khellida Loiane V. Ramos-Rocha; Khellida Loiane V. Ramos-Rocha; Michelle Alvares Sarcinelli; Marcelo Henrique da Cunha Chaves; Helvécio Vinícius Antunes Rocha; Patrícia Léo; Natália Neto Pereira Cerize; Maria Helena Ambrosio Zanin; Valker Araujo Feitosa; Carlota de Oliveira Rangel-Yagui (Frontiers Media S.A., 2024)
The COVID-19 pandemic has raised concern regarding respiratory system diseases and oral inhalation stands out as an attractive non-invasive route of administration for pulmonary diseases such as chronic bronchitis, cystic fibrosis, COVID-19 and community-acquired pneumonia. In this context, we encapsulated azithromycin in polycaprolactone nanoparticles functionalized with phospholipids rich in dipalmitoylphosphatidylcholine and further produced a fine powder formulation by spray drying with monohydrated lactose. Nanoparticles obtained by the emulsion/solvent diffusion-evaporation technique exhibited a mean hydrodynamic diameter around 195-228 nm with a narrow monomodal size distribution (PdI < 0.2). Nanoparticle dispersions were spray-dried at different inlet temperatures, atomizing air-flow, aspirator air flow, and feed rate, using lactose as a drying aid, resulting in a maximal process yield of 63% and an encapsulation efficiency of 83%. Excipients and the dry powder formulations were characterized in terms of morphology, chemical structure, thermal analyses and particle size by SEM, FTIR, DSC/TGA and laser light diffraction. The results indicated spherical particles with 90% at 4.06 µm or below, an adequate size for pulmonary delivery. Aerosolization performance in a NGI confirmed good aerodynamic properties. Microbiological assays showed that the formulation preserves AZM antimicrobial effect against Staphylococcus aureus and Streptococcus pneumoniae strains, with halos above 18 mm. In addition, no formulation-related cytotoxicity was observed against the human cell lines BEAS-2B (lung epithelial), HUVEC (endothelial) and HFF1 (fibroblasts). Overall, the approach described here allows the production of AZM-PCL nanoparticles incorporated into inhalable microparticles, enabling more efficient pulmonary therapy of lung infections.